Organizational Conflict Management: The All Important Public Universities Performance Strategy Under Neglect in Kenya - Gertrude Muthoni , Mwaniki; Muathe, Stephen, M. A. (European Scientific Journal, ESJ, 2021)
Workplace conflicts are inevitable in any work-organization. However, there is contestation as to whether management of organizational conflicts enhances or deteriorates employees’ performance. This study sought to determine the effect of organizational conflict management techniques, namely negotiation, mediation, collaboration and avoidance, on employees’ performance in selected public universities in Kenya. The study was based on the human relations, human capital and contingency theories. The study adopted a positivist quantitative approach - a methodological approach that seeks to quantify data and generalize results from a sample of a target population in an objective manner using statistical means. The study adopted descriptive research design. The study population was employees of the selected public universities in Kenya. A sample of 160 participants was chosen using stratified and simple random sampling methods. Gathered data was analyzed using descriptive and inferential statistics with the help of the Statistical Package for Social Sciences. Both ANOVA and regression analysis were utilized in analysis of the data. The study established that there was a strong positive and significant relationship between negotiation, mediation as well as collaboration and employees’ performance in the selected public universities in Kenya as the three variables had positive beta coefficients and p-values less than the set significance level threshold. However, avoidance was found to have a negative and significant relationship with employees’ performance in the selected public universities in Kenya as denoted by its negative beta coefficient value and a p value less than the set significance level threshold. The study concluded that negotiation, mediation and collaboration positively influenced employees’ performance while avoidance adversely affected employees’ performance. Consequently, the study recommends that the managements of public universities in Kenya may apply a mix of these organizational conflict management techniques to achieve optimal outcomes in resolution of organizational conflicts.